Strategies of a guidance and counseling teacher in Shaping Student Character - Nurul, Nurul Muzakkiyah; Uswatun Hasanah (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2021)
Indonesia is currently experiencing various problems. These problems cannot be separated from the existing educational process. Problems caused by several factors, one of which is the lack of internalization of values in education. Currently, the existing educational process only emphasizes the scientific aspects and intelligence of students. As for the moral and ethical aspects as the basis for the formation of national character and culture, they are not given much attention. The purpose of this study was to find out the guidance and counseling teacher's strategies in shaping student morals and the methods used in instilling them. The subjects studied were Class XI Students at MA. Hasan Jufri Bawean is a school located in the Hasan Jufri boarding school environment located in Lebak Village, precisely in Kebun Agung Hamlet, Sangkapura District, Pulau Bawean, Gresik Regency. This type of qualitative research uses descriptive methods, where data is obtained through interviews and observations involving counseling teachers. The results show that effective and efficient counseling is also a habit for students to acquire student habits or morals. In addition, BK teachers also use applied methods such as giving examples and exemplary and habituation in order to realize student morals. Research has implications for the discovery of values instilled in students to shape student morals. The strategy applied in instilling these values can also be a new alternative in the world of education, especially in efforts to shape student morals.